Minimising Warm and Cold Ischaemic Times in Livers Transplanted from Donation after Circulatory Death Donors: Are We Doing Enough?. (October 2014) - Coulter, Colin
Warm and cold ischaemic times (WIT and CIT) are two modifiable factors known to have a significant impact on transplant graft survival. The aim of this study was to investigate the changes in WIT and CIT in our unit, and to study whether there was any correlation between them and the outcomes of donation after circulatory death (DCD) liver transplantation. Data was collected by a single-centre retrospective review of all DCD livers transplanted at our unit (n=61) from 2004–2011. The outcome measures were graft survival at one week, three months and one year post-transplant. Each year the CIT and WIT remained relatively constant, with no statistically significant change (p=0.3 and p=0.36 respectively). From 2004–2011, one graft failed within seven days of transplant, two grafts failed within three months and four failed within one year. A statistically significant finding was a correlation between WIT and graft failure at one year post-transplant (p=0.02) with an odds ratio of 0.76 (95% confidence interval 0.59–0.98), which suggested that for each additional minute of WIT, the chance of graft failure at one year increased by 24%. This single-centre study demonstrated a failure to effectively minimise WIT and CIT over eight years in this unit. Our results show that reductions in WIT can have a significant impact on the long-term outcome of DCD liver transplantation. This study has identified modifiable factors which can reduce the overall CIT and WIT affecting livers for DCD transplantation.